Trabalho escravo contemporâneo no Maranhão: uma análise da Lista Suja do Ministério do Trabalho como ação de repressão econômica - ARAÚJO, Bruna Feitosa Serra de (2021)
The present thesis has as its scope the analysis of contemporary slave labor in Maranhão, with regard to the Dirty List of the Ministry of Labor as an action of economic repression. It analyzes the capital-labor relationship and contemporary slavery, as well as the historical context of neo-slavery and its normative repercussions, going through the invisibility of slave labor and its recognition and condemnation as the first country to be condemned in the Inter-American Court of Human Rights for violation of the San José Pact of Costa Rica. There is a regulatory framework for confronting slave labor at the international, national and state levels. Maranhão is observed in the contemporary representation of slavery and it is understood that victimization for slave labor is linked to the cultural roots that for centuries have tolerated this type of exploitation, added to impunity, the lack of professional qualification and the geographical isolation that favor this type of conduct in certain regions of the state, making Maranhão the state with the largest number of workers who are victims of this crime in Brazil. The fundamental factors for the configuration of contemporary slavery in Maranhão are analyzed: precision, as an environment conducive to slavery, the economic model that concentrates income and generates social exclusions and impunity as a factor of social injustices. The Dirty List is approached as an action of economic repression of the 2nd National Plan for the Eradication of Slave Labor as a public policy, going through the analysis of the guarantee of effectiveness to the fundamental right to information (Law of Access to Information) and the arguments of the Supreme Federal Court (STF), which in its decisions now prohibits, now authorizes the publication of the register of employers who kept workers reduced to the condition analogous to slavery, carrying out a careful analysis of the favorable and unfavorable arguments, culminating in the Supreme Court with the constitutionality of the Dirty List in September 2020. Remedial measures are addressed in an attempt to reverse the high data on recurrence of work in conditions analogous to that of slaves, through programs that within the scope of their competences aim to consolidate a set of actions to combat this social wound , such as the granting of unemployment insurance, enrollment in the Single Registry (CadÚnico) for Programs Social Funds of the Federal Government (Bolsa Família), insertion in the Specialized Reference Center for Social Assistance (CREAS), inclusion as a beneficiary of Agrarian Reform settlement and the implementation of Rural Credit (PRONAF) as financing for family farming activities.